2019
DOI: 10.3389/fphys.2019.00153
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Duration and Frequency Determines AKI-to-CKD Progression Monitored by Dynamic Changes of Tubular Biomarkers in IRI Mice

Abstract: Ischemia reperfusion injury (IRI) is one of the most common causes of acute kidney injury (AKI). However, the pathogenesis and biomarkers predicting the progression of IRI-induced AKI to chronic kidney disease (CKD) remain unclear. A side-by-side comparison between different IRI animal models with variable ischemic duration and episodes was performed. The dynamic changes of KIM-1 and NGAL continuously from AKI to CKD phases were studied as well. Short-term duration of ischemia induced mild renal tubule-interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 43 publications
1
77
1
1
Order By: Relevance
“…The mesangial matrix index was calculated and graded as follows: 0 represents no lesion; 1 + represents sclerosis of <25% of the glomerulus; and 2+, 3+, and 4+ represent sclerosis of >25‐50, >50‐75, and >75% of the glomerulus, respectively 33 . Tubular injury was defined and calculated as follows: score 0: no tubular injury; score 1: < 10% of tubules injured; score 2:10%‐25% of tubules injured; score 3:25%‐50% of tubules injured; score 4:50%‐74% of tubules injured; score 5: > 75% of tubules injured, as previously described 36,37 . For IHC staining, sections were treated with diaminobenzidine or NovaRed substrate (DAKO Labs, K3468), followed by counterstaining with Mayer hematoxylin and examination.…”
Section: Methodsmentioning
confidence: 99%
“…The mesangial matrix index was calculated and graded as follows: 0 represents no lesion; 1 + represents sclerosis of <25% of the glomerulus; and 2+, 3+, and 4+ represent sclerosis of >25‐50, >50‐75, and >75% of the glomerulus, respectively 33 . Tubular injury was defined and calculated as follows: score 0: no tubular injury; score 1: < 10% of tubules injured; score 2:10%‐25% of tubules injured; score 3:25%‐50% of tubules injured; score 4:50%‐74% of tubules injured; score 5: > 75% of tubules injured, as previously described 36,37 . For IHC staining, sections were treated with diaminobenzidine or NovaRed substrate (DAKO Labs, K3468), followed by counterstaining with Mayer hematoxylin and examination.…”
Section: Methodsmentioning
confidence: 99%
“…64 A single-centre study in 30 paediatric patients (1-6 years old) who underwent cardiac surgery reported lower GFR and higher AKI incidence based on serum creatinine measurements obtained 5 minutes and 2 hours after weaning from cardiopulmonary bypass. [66][67][68] Their use in studies on the role of sympathetic activation may improve translatability of experimental data. In contrast to experimental renal IR studies where conditions can be well standardized, the effects of sympatholytics may have been blurred by the complexity of clinical scenarios and factors such as patient age, genetic diversity, associated chronic diseases and diverse co-medications.…”
Section: Of 10mentioning
confidence: 99%
“…3 Currently, reverse translational approaches are taken to better match animal models of renal IR to clinical situations that cause AKI. [66][67][68] Their use in studies on the role of sympathetic activation may improve translatability of experimental data.…”
Section: Clinical Akimentioning
confidence: 99%
“…Renal ischemia/reperfusion (IR) injury is a major cause of AKI, characterized by apoptosis, in ammation and immune responses associated damage (Bellomo et al, 2012;Dong et al, 2019). Recently, the innate repair mechanism in AKI has attracted great attention, which is highlighted by an innate repair receptor, a heterodimer of erythropoietin (EPO) receptor and β common receptor (EPOR/βcR) (Brines and Cerami 2012).…”
Section: Introductionmentioning
confidence: 99%